Shwachman-Diamond Syndrome and Diabetes: An Update from the Italian Registry and Review of the Literature - Minelli, Antonella; Pintani, Emily; Valli, Roberto; Tridello, Gloria; Porta, Giovanni; Fioredda, Francesca; Cipolli, Marco; Danesino, Cesare (Experimental and Clinical Endocrinology & Diabetes, 2025)
The issue of a possible association between Shwachman-Diamond Syndrome and diabetes has been debated for many years. This review updates the Italian Shwachman-Diamond registry, confirming our previous findings that suggest that these patients might be at higher risk of developing diabetes, particularly type 1. These data are of relevance in the clinical follow-up of patients in everyday life, emphasizing the need for early diagnosis and timely intervention.
Keywords: exocrine pancreatic insufficiency; bone marrow dysfunction; ribosomopathy; glucose tolerance test; type 1 diabetes; type 2 diabetes